Vitamin D Status Is Not Associated with Outcomes of Experimentally-Induced Muscle Weakness and Pain in Young, Healthy Volunteers - Susan M. Ring; Erin A. Dannecker; Catherine A. Peterson (Journal of Nutrition and Metabolism)
Vitamin D receptors have been identified in skeletal muscle; and symptoms of vitamin D deficiency include muscle weakness and pain. Moreover, increased serum 25-hydroxyvitamin D (25(OH)D) concentrations have been associated with improved muscle function. To further clarify the importance of vitamin D to muscle, we examined the association between vitamin D status and exercise-induced muscle pain and weakness in healthy people. Muscle damage to the elbow flexors was induced with eccentric exercise (EE) in 48 individuals (22.5 ± 3.2 yrs). Muscle pain ratings following unloaded movement and peak isometric force (IF) were collected before EE and for 4 days post-EE. Linear regression was used to determine if serum 25(OH)D was a predictor of any outcome. In males, R2-values from 0.48 to 1.00. R2 for IF ranged from 0 to 0.02 and P-values from 0.48 to 1.00. In females, R2 for pain ratings ranged from 0.01 to 0.11 and P-values from 0.14 to 0.59. R2 for IF ranged from 0 to 0.04 and P-values from 0.41 to 0.90. In conclusion, vitamin D status did not predict muscle pain or strength after EE-induced muscle damage in young healthy men and women.